Вплив обробки ультразвуковим випромінюванням наноалмазу детонаційного синтезу на його термостійкість - Богатирьова, Г.П.; Забуга, В.Я.; Цапюк, Г.Г.; Панова, А.М.; Бєда, О.А.; Шевченко, Н.О. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
Authors studied influence of ultrasonic radiation on physical-chemical properties of synthetic diamond nanopowders. A diamond was got the method of detonation synthesis. Job performances rotined that over ultrasonic treatment brings to diminishing of active groups and centers on-the-spot diamond nanopowders.